Fabrication of polyimide composite films based on carbon black for high‐temperature resistance. Issue 11 (25th January 2014) - Kwon, Jinuk; Kim, Jinyoung; Lee, Jeeeun; Han, Patrick; Park, Dongmyung; Han, Haksoo
<x xml:space="preserve">Abstract</x> A novel high‐performance material, carbon black (CB) polyimide (PI), was obtained by the chemical synthesis of CB (carbon black N326) with PI. Following its synthesis, several analyses were carried out to investigate the thermal and mechanical properties of the newly synthesized CB‐PI. The thermal decomposition temperature of CB‐PI compared to PI increased by 76°C from 508 to 584°C. The glass transition temperature of CB‐PI as evaluated by differential scanning calorimetry increased by 204°C from 379 to 583°C compared to that of PI. Moreover, the mechanical strength of CB‐PI increased by 16% compared to that of PI. In addition, the analyses confirm that CB and PI in the synthesized CB‐PI were chemically crosslinked, which was shown to be responsible for the superior thermal and mechanical properties of the CB‐PI. POLYM. COMPOS., 35:2214–2220, 2014. © 2014 Society of Plastics Engineers